WEBVTT
00:00:00.990 --> 00:00:07.620
Given that π¦ minus three π₯ equals seven, calculate the value of π₯ when π¦ equals three.
00:00:09.070 --> 00:00:12.910
We start with our equation π¦ minus three π₯ equals seven.
00:00:13.640 --> 00:00:16.000
And then, we plug in three for π¦.
00:00:17.270 --> 00:00:21.090
Our new equation says three minus three π₯ equals seven.
00:00:21.990 --> 00:00:23.450
We want to solve for π₯.
00:00:23.450 --> 00:00:25.800
And that means weβll need to get π₯ by itself.
00:00:26.560 --> 00:00:29.730
The next step will be subtracting three from both sides.
00:00:30.730 --> 00:00:33.600
On the left, three minus three equals zero.
00:00:34.160 --> 00:00:35.520
They cancel each other out.
00:00:36.330 --> 00:00:40.420
And on the right, seven minus three equals four.
00:00:41.460 --> 00:00:43.800
Again, weβre trying to isolate π₯.
00:00:44.720 --> 00:00:47.810
Here, π₯ is being multiplied by negative three.
00:00:48.180 --> 00:00:54.630
To isolate this, weβll divide by negative three on both sides of the equation.
00:00:55.200 --> 00:00:58.340
Negative three divided by negative three equals one.
00:00:58.480 --> 00:00:59.620
They cancel out.
00:01:00.390 --> 00:01:07.950
π₯ equals four divided by negative three, which we can rewrite as negative four-thirds.
00:01:09.500 --> 00:01:14.220
When π¦ equals three, π₯ is equal to negative four-thirds.